Some Key Issues for Understanding and Interpreting Criminal Procedure Rules Limiting Property Rights. - Amiryan, Karen (Bulletin of Yerevan University C: Jurisprudence, 2024)
The purpose of the article is to analyze a number of issues related to the legitimacy of restrictions on property rights as prescribed by the Criminal Procedure Code of the Republic of Armenia. The article refers to a number of regulations related to the material grounds and procedures for imposing attachment on the assets as prescribed by Chapters 15 and 39 of the Criminal Procedure Code of the Republic of Armenia dated June 30, 2021, which are perceived and interpreted in different ways. In other words, the article aims to present the issues that have arisen in law enforcement practice. In this sense, the article is also relevant, since the presented approaches may be of interest to the students, lawyers, law enforcement authorities, and judges.The article is dedicated to a number of problems related to the legality of decisions to recognize property of alleged criminal origin as physical evidence, which are encountered in legal practice.In the second part of the article, the discussed issues such as the removal of prohibited property under the conditions of the former Criminal Procedure Code of the Republic of Armenia under the conditions of the current Criminal Procedure Code of the Republic of Armenia, making a note of the sufficient value of the property with the decision to prohibit the property (the second part of the Article will be published in the "Legality" of the Prosecutor's Office of the Republic of Armenia in the periodical).
Keywords: right of ownership; limitation of right of ownership; judicial guarantees; material evidence; prohibition of property; lifting attachment from the assets